A Universal Design Strategy Based on NiPS3 Nanosheets towards Efficient Photothermal Conversion and Solar Desalination - Wang, Honglei; Bo, Yifan; Klingenhof, Malte; Peng, Jiali; Wang, Dong; Wu, Bing; Pezoldt, Jörg; Cheng, Pengfei; Knauer, Andrea; Hua, Weibo; Wang, Hongguang; van Aken, Peter A.; et al. (Advanced Functional Materials, 2023)
2D nanomaterials are proposed as promising photothermal materials for interfacial photothermal water evaporation. However, low evaporation efficiency, the use of hazardous hydrofluoric solution, and poor stability severely limit their practical applications. Here, a mixed solvent exfoliation surface deposition (MSESD) strategy for the preparation of NiPS3 nanosheets and NiPS3/polyvinyl alcohol (PVA) converter is successfully developed. The converter is obtained by drop-casting the NiPS3/PVA nanosheets onto a sponge. The PVA is mainly deposited on the edge of NiPS3 nanosheets, which not only improves the stability of NiPS3 nanosheets, but also adheres to the sponge to prepare a 3D photothermal converter, which shows an evaporation rate of 1.48 kg m−2 h−1 and the average photothermal conversion efficiency (PTCE) of 93.5% under a light intensity of 1 kW m−2. The photothermal conversion mechanism reveals that the energy of absorbed photons in NiPS3 nanosheets can be effectively converted into heat through non-radiative photon transitions as well as multiple optical interactions. To the best of the knowledge, this is the first report on the application of 2D metal-phosphorus-chalcogen (MPChx) for solar desalination, which provides new insights and guidance for the development of high-performance 2D photothermal materials.
CRIS-Team Scopus Importer:2023-11-17
Keywords: 2D materials; desalination; NiPS; photothermal conversions; surface depositions